Innovative Outreach Services by Dukcapil Peduli for Vulnerable Groups: A Case Study of Mutiara Sukma Mental Hospital in Mataram City - Rahmad Hidayat; Nadia Irawati; Cahyadi Kurniawan (Journal of Public Power, 2026)
A study on population administration accessibility noted that e-KTP ownership among ODGJ in 2022 is estimated to only reach around 35% of the total national ODGJ population. Meanwhile, data services in several regions show gradual progress, such as in Mandailing Natal Regency, which saw an increase in e-KTP ownership for people with disabilities from 47.76% in 2021 to 55.52% in 2022, increasing to 61.35% in 2023, and reaching 70.97% in 2024. This study aims to describe the implementation of the Dukcapil Peduli program at Mutiara Sukma Mental Hospital in Mataram City and to identify the inhibiting factors encountered during its implementation. The study employed a qualitative case study approach using participatory observation, in-depth interviews, and documentation techniques. The findings indicate that this locus-based outreach service program successfully increased e-KTP ownership among vulnerable groups through the utilization of SIKEL (Interactive Service Activity Facility) and MOBILO (Mobile Online Service Vehicle). The program proved effective in reducing administrative access barriers through cross-sector collaboration between the Civil Registration Office and the mental hospital. Nevertheless, the implementation still encountered technical obstacles, particularly damage to portable biometric devices and internet network disruptions in the field. This study implies that inclusive and proactive public services can significantly expand civil rights access for vulnerable communities and may serve as a model for population administration service innovation in other regions. However, the study is limited by its single-case design; therefore, future studies are recommended to apply comparative approaches across multiple regions to further examine the effectiveness and scalability of the service model.